Calidad regulatoria en Perú: de la simplificación administrativa al análisis de impacto regulatorio en cámara lenta - Quintana Sánchez, Eduardo (2021)
This paper reviews and discusses a wrong distinction that has arisen in Peru —at both legal and conceptual levels— between (i) the so-called regulatory quality analysis, even though it is only an additional administrative simplification tool, and (ii) the improvement of regulatory quality through several tools including regulatory impact assessment —RIA. With this aim, it describes the concepts and initiatives implemented by the best international practices concerning, on one hand RIA as a cornerstone to ensure the quality of substantive regulations —economic and social regulations— and on the other hand, administrative simplification tools to reduce red tape as complementary measures. Likewise, it explains the developments in administrative simplification in Peru, including the launching of the so-called regulatory quality analysis program 5 years ago, reducing it only to a —more sophisticated administrative simplification tool. This paper describes also the scattered and ineffective initiatives on RIA that have been carried out in Peru, as well as the latest RIA regulation which is still a fragile effort to effectively implement an integral regulatory reform. In sum, Peruvian regulatory reform has prioritized ancillary mechanisms rather than substantive ones. The mandate to enforce RIA is weak because it has been only passed by a regulation rather than a law, and the approval of relevant provisions to make RIA effective may still be delayed. Therefore, regulatory reform is yet incomplete, vulnerable, and focused on administrative simplification.